Antibacterial Activity of Ethanol Extract of Thorn Spinach Leaves (Amaranthus spinosus L.) against Streptococcus mutans - Setiani, Ria Dwi; Trimulyono, Guntur (LenteraBio : Berkala Ilmiah Biologi, 2024)
Dental caries is a disease that attacks oral health that many people suffer from. Dental caries is caused by the activity of the bacteria Streptococcus mutans. Thorn spinach (Amaranthus spinosus L.) is a medicinal plant that has secondary metabolite compounds that can have antibacterial properties. This research aims to determine the antibacterial activity and optimal concentration in inhibiting the growth of S. mutans. The stages of this research include preparation, extraction, making sample solutions, phytochemical screening, rejuvenation and making bacterial suspensions, as well as antibacterial activity tests. The antibacterial activity test used extract concentrations of 20%, 40%, 60% and 80%. These extract concentrations produced an average diameter of the inhibition zone 0.25 ± 0.50 mm; 1.50 ± 2.38 mm; 5.13 ± 0.75 mm; and 6.38 ± 0.25 mm. Data were analyzed using the Kolmogorov-Smirnov test, Duncan test, and Anova test. Based on the analysis data, it was concluded that there was antibacterial activity at each extract concentration, the concentration that produced the highest average diameter was the 80% concentration, but statistically it was not significantly different from the 60% concentration. This research proves the ability of thorn spinach leaves to inhibit the growth of S. mutans which causes dental caries.